What factors affect acceptance attitudes towards vaccination amidst a major public health crisis? A national cross-sectional study - Feng Ying Zhang; Li nan Cheng; Xiao feng Xie; Jianhui Kong (BMJ Open)
Objectives Vaccine hesitancy persists as a significant global health concern, especially during public health crises. This study aimed to explore factors influencing vaccination acceptance during a major public health crisis and establish a model of influencing factors.Design A cross-sectional study.Methods An anonymous cross-sectional survey was conducted online, encompassing sociodemographic characteristics, anxiety levels, personal risk perception and attitudes towards vaccination acceptance. Data analysis was performed using t-tests, one-way analysis of variance and multiple linear regression techniques in IBM SPSS Statistics V.25.0 (IBM Corp., Armonk, NY, USA).Results A total of 3921 participants participated in the survey. The mean acceptance attitudes were above the moderate level (M=4.02, SD=0.51), the mean risk perception score was below the moderate level (M=2.66, SD=0.58), and the mean score on the Self-Rating Anxiety Scale was also below the moderate level (M=2.05, SD=0.53). The results showed that internal variables (gender, age, marital status, professional background, region) and external variables (average family income, distance from home to vaccination site, family medical background) were statistically significant (p<0.05). Gender, region, distance from home to the vaccination site, anxiety, family medical background, risk coping, emotional perception and psychological representation of unusual severity were identified as significant predictors of vaccination acceptance attitudes, with the model explaining 35% of the variance (R²= 0.35, adjusted R²= 0.33). Based on these results, we constructed a theoretical model of influencing factors for vaccine acceptance attitudes.Conclusions Despite increased acceptance of vaccination during major public health events, factors that both support and hinder acceptance remain. Identifying these factors allows for effective disease control and informs the development of public health strategies and crisis response measures.